2018
DOI: 10.1101/411470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of Replication Origins in Vertebrate Genomes: Rapid Turnover Despite Selective Constraints

Abstract: Background:The replication programme of vertebrate genomes is driven by the chromosomal distribution and timing of activation of tens of thousands of replication origins. Genome-wide studies have shown the frequent association of origins with promoters and CpG islands, and their enrichment in G-quadruplex sequence motifs (G4). However, the genetic determinants driving their activity remain poorly understood. To gain insight on the functional constraints operating on replication origins and their spatial distri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…3h). This is in accordance with the presence of an origin G-rich Repeated Element (OGRE) 2 or tandemly arranged multiple (up to 6-12) G4 structures as well as ultra-short C/G-rich nucleotide motifs found at human, mouse and chicken origins 35 .…”
Section: Resultssupporting
confidence: 83%
“…3h). This is in accordance with the presence of an origin G-rich Repeated Element (OGRE) 2 or tandemly arranged multiple (up to 6-12) G4 structures as well as ultra-short C/G-rich nucleotide motifs found at human, mouse and chicken origins 35 .…”
Section: Resultssupporting
confidence: 83%
“…RT profiles obtained from S1 to S4 fractions showed that the IZ about 30 kb upstream of the site of insertion (IZ.1) is activated in S3 in WT cells, whereas the IZ located 60 kb downstream (IZ.2) is activated already in S2. IZ.1 and IZ.2 correspond to strong initiation sites detected by the short nascent strand (SNS) assay (Massip et al , 2019). Profiles observed at the same region in a cell line modified on both chromosomes (2 × ( β A ‐globin + β‐actin ) cell line) showed firing of the IZ.1 in S1, whereas the IZ.2 is unchanged compared to the WT cell line.…”
Section: Resultsmentioning
confidence: 99%
“…NS‐enriched and depleted regions for each fraction are represented in purple and blue, respectively. Single reads form SNS aligned and track of replication origins (Ori peaks) determined in (Massip et al , 2019) are reported in between. The three mid‐late insertion sites 1, 2, and 3 are indicated with red arrows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RefSeq genes coordinates were extracted from the UCSC Genome Browser; pLi scores were extracted from the gnomAD dataset (Lek et al 2016). Annotation was also made across lamina associated domains (LADs) (Guelen et al 2008); topologically associated domains (TADs) (Rao et al 2014); repeated elements (RepeatMasker); chromosomal cytoband and Giemsa staining (Furey and Haussler 2003); chromosomal common fragile sites (Fungtammasan et al 2012); replication origins (Massip et al 2019); A/B compartments (Fortin and Hansen 2015) and replication timing (Dixon et al 2018). For the latter, only constitutive early and late domains were considered.…”
Section: Breakpoint and Junction Annotationmentioning
confidence: 99%